MULTILAYER PLASTIC RECONSTRUCTION IN THE THREE-DIMENSIONAL STUDY OF THE HUMAN LACRIMAL GLAND - Hryn, V.H.; Sherstiuk O.О.; Piliuhin, A.V.; Svintsytska, N.L.; Lavrenko, A.V. (World of Medicine and Biology, 2018)
Lacrimal glands are in the limelight for both clinicians, and morphologists, who understand that the clinical interpretation of morphological factology is to be relying on modern anatomical data. 10 specimens of the human lacrimal glands (palpebral part) have been studied. The use of the method of multilayer plastic reconstruction enables to get the megascopic reconstruction of the lacrimal gland, which can be studied from all sides, getting a visualization of the shape and dimensions, as well as allows to investigate the inner topography of the organ, the geometry of the lumen of the epithelial excretory ducts of the glands, to determine the changes in the thickness of the wall, to get a visual representation of microtopographic correlation between the different sections of the blood microcirculatory flow with the epithelial excretory ducts in the human lacrimal glands.